STING Induces Liver Ischemia-Reperfusion Injury by Promoting Calcium-Dependent Caspase 1-GSDMD Processing in Macrophages. (30th January 2022) - Wu, Xin-yi; Chen, Ya-jun; Liu, Chang-an; Gong, Jun-hua; Xu, Xue-song
Abstract : Objectives . Although a recent study reported that stimulator of interferon genes (STING) in macrophages has an important regulatory effect on liver ischemia-reperfusion injury (IRI), the underlying mechanism of STING-dependent innate immune activation in liver macrophages (Kupffer cells, KCs) remains unclear. Here, we investigated the effect of STING on liver macrophage pyroptosis and the associated regulatory mechanism of liver IRI. Methods . Clodronate liposomes were used to block liver macrophages. AAV-STING-RNAi-F4/80-EGFP, an adenoassociated virus (AAV), was transfected into the portal vein of mice in vivo, and the liver IRI model was established 14 days later. In vitro, liver macrophages were treated with STING-specific siRNA, and a hypoxia-reoxygenation (H/R) model was established. The level of STING was detected via Western blotting (WB), RT-PCR, and immunostaining. Liver tissue and blood samples were collected. Pathological changes in liver tissue were detected by hematoxylin and eosin (H&E) staining. Macrophage pyroptosis was detected by WB, confocal laser scanning microscopy (CLSM), transmission electron microscopy (TEM), and enzyme-linked immunosorbent assay (ELISA). The calcium concentration was measured by immunofluorescence and analyzed with a fluorescence microplate reader. Results . The expression of STING increased with liver IRI but decreased significantly after the clodronate liposome blockade of liver macrophages. After knockdown of STING, the activation of caspase 1-GSDMD in macrophages and liver IRI was alleviated. More interestingly, hypoxia/reoxygenation (H/R) increased the calcium concentration in liver macrophages, but the calcium concentration was decreased after STING knockdown. Furthermore, after the inhibition of calcium in H/R-induced liver macrophages by BAPTA-AM, pyroptosis was significantly reduced, but the expression of STING was not significantlydecreased. Conclusions . Knockdown of STING reduces calcium-dependent macrophage caspase 1-GSDMD-mediated liver IRI, representing a potential therapeutic approach in the clinic.